2017
DOI: 10.1039/c7ob00854f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, resolution, and in vitro evaluation of three vesicular acetylcholine transporter ligands and evaluation of the lead fluorine-18 radioligand in a nonhuman primate

Abstract: Vesicular acetylcholine transporter (VAChT) is a reliable biomarker for assessing cholinergic dysfunction associated with dementia. We recently reported three new potent and selective carbon-11 labeled VAChT radiotracers. Herein, we report the resolution with a Chiralcel OD column of three additional fluorine containing VAChT ligands in which a fluoroethoxy or fluoroethylamino moiety was substituted for the methoxy group. An in vitro competitive binding assay showed (−)-7 had high potency for VAChT (Ki-VAChT =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The influence of enantioselectivity of the vesamicol analogs FEOBV ( 2 ) [ 45 ], MIBT ( 8 ) [ 55 ], FBT ( 9 ) [ 60 ], oIV ( 10 ) [ 62 ], OMV ( 11 ) [ 63 ], OIDV ( 13 ) [ 67 ], FBBV ( 18 ) [ 78 ], 19 [ 81 ], TZ659 ( 20 ) [ 82 ], VAT ( 21 ) [ 83 ], and 22 [ 84 ] on the binding affinity for VAChT, σ 1 , and σ 2 receptors was reported. The investigated vesmicol analogs except for MIBT ( 8 ) and FBT ( 9 ) showed that (−)-enantiomers had about 3- to 29-fold higher binding affinity for VAChT than (+)-enantiomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of enantioselectivity of the vesamicol analogs FEOBV ( 2 ) [ 45 ], MIBT ( 8 ) [ 55 ], FBT ( 9 ) [ 60 ], oIV ( 10 ) [ 62 ], OMV ( 11 ) [ 63 ], OIDV ( 13 ) [ 67 ], FBBV ( 18 ) [ 78 ], 19 [ 81 ], TZ659 ( 20 ) [ 82 ], VAT ( 21 ) [ 83 ], and 22 [ 84 ] on the binding affinity for VAChT, σ 1 , and σ 2 receptors was reported. The investigated vesmicol analogs except for MIBT ( 8 ) and FBT ( 9 ) showed that (−)-enantiomers had about 3- to 29-fold higher binding affinity for VAChT than (+)-enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…22 is a vesamicol analog that incorporated the fluoroethyl amino group instead of the methylamino group into (−)-TZ659 ( 20 ) [ 84 ]. The affinity (Ki) of ( 22 ) to VAChT, σ 1, and σ 2 was 0.31 nM (PC12 A123.7 cells which express human VAChT), 1,870 nM (Guinea pig brain), and 5,480 nM (rat liver), respectively.…”
Section: Vacht Imaging Agent Based On Vesamicol Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions were monitored by thin-layer chromatography (TLC) and visualized under ultraviolet light (l = 254). Flash column chromatography was performed using Silica Flash P60 silica gel (40-63 mm) from Silicycle Inc. 1 Ha nd 13 CNMR spectra were recorded on Varian 400 and 300 MHz instruments. Chemical shifts were reported in parts per million (ppm) and calibrated using the residual undeuterated solvent as an internal reference (CDCl 3 : d = 7.26 ppm;C D 3 OD: d = 3.31 ppm;[ D 6 ]DMSO: d = 2.50 ppm).…”
Section: Methodsmentioning
confidence: 99%
“…[10] To test the hypothesis that incorporating sulfur into VAChT radiotracer would alter the in vivo pharmacologic properties, we interposed sulfur-containing moieties such as thioether, sulfoxide, sulfone, and sulfamide into the carbonyl-containing pharmacophore structures represented by lead VAChT radiotracers, (-)-[ 18 F] 4 and (-)-[ 11 C] 5 (Figure 1). [11, 12, 13] In current manuscript, we reported our efforts on the syntheses and in vitro biological evaluation of these new sulfur-containing analogues, the radiosyntheses and in vivo evaluation in rodent of representative (-)-[ 11 C] 8 and (-)-[ 18 F] 14a , as well as microPET study of (-)-[ 11 C] 8 in the brain of non-human primate (NHP).…”
Section: Introductionmentioning
confidence: 99%